FIBROMYXOID SARCOMA IN RATTUS NORVEGICUS: CASE REPORT: CASE REPORT - FERREIRA, C. S.; JACIK, S. C. C.; MENEZES, R. C.; SCHIAVI, G. S.; BAUMGARTNER, V. F. P. R.; CALEFI, A. S. (Ars Veterinaria, 2023)
Myxoid sarcoma comprises malignant tumors of myxoid origin. Low-Grade Fibromyxoid Sarcoma (LGFM) has benign histopathological characteristics, slow growth, but with high metastatic potential. There are at least 25 cases of LGFM in humans, being more common in the deep intramuscular region, mainly in the thigh and trunk, but it has also been described in the retroperitoneum, mesentery and renal capsule. In December 2022, a 2-year-old male Wistar rat (Rattus norvegicus) had difficulty walking and a nodule was noted in the dorsal region of the left pelvic limb, measuring 2.5 cm x 3 cm. In January 2023, amputation was performed and the morphological diagnosis obtained was myxoid sarcoma. In February 2023, formation was observed in the left renal capsule measuring 2cm, growing to 6cm in May 2023, with the same diagnosis as that of the limb. The tutors opted for the surgical removal of the neoformation, however, the animal evolved to death, being referred for necroscopic examination. The case represents the first worldwide case of LGFM in Wistar, the second reported in animals.